2018
DOI: 10.1155/2018/4830659
|View full text |Cite
|
Sign up to set email alerts
|

Spectral CT Analysis of Solitary Pulmonary Nodules for Differentiating Malignancy from Benignancy: The Value of Iodine Concentration Spatial Distribution Difference

Abstract: Objective The objective is to assess the value of spatial distribution difference in iodine concentration between malignant and benign solitary pulmonary nodules (SPNs) by analyzing multiple parameters of spectral CT. Methods Sixty patients with 39 malignant nodules and 21 benign nodules underwent chest contrast CT scans using spectral imaging mode during pulmonary arterial phase (PP), arterial phase (AP), and venous phase (VP). Iodine concentrations of proximal and distal regions in pulmonary nodules on iodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…According to our results, the value of NIC was greater in the malignant group than in the benign group, and NIC VP was superior in differentiating malignant from benign nodules. This result was similar to the findings of previous studies that demonstrated the sensitivity and specificity of NIC VP to be in the ranges of 93-93.8% and 85.7-95%, respectively (4,(17)(18)(19). Xiao et al (18) focused on the value of kVp-switching dual-energy CT in SPN diagnosis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…According to our results, the value of NIC was greater in the malignant group than in the benign group, and NIC VP was superior in differentiating malignant from benign nodules. This result was similar to the findings of previous studies that demonstrated the sensitivity and specificity of NIC VP to be in the ranges of 93-93.8% and 85.7-95%, respectively (4,(17)(18)(19). Xiao et al (18) focused on the value of kVp-switching dual-energy CT in SPN diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, Zhang et al (4) reported that NIC was a more valuable index than λ HU and that CT numbers, especially in the VP, demonstrated a sensitivity and specificity of 93.8% and 85.7%, respectively. Another study regarding the distribution difference of iodine concentration between malignant and benign SPNs found that the differences in NIC (dNIC) between the proximal and the distal regions in the VP were optimal in the characterization of SPNs, with a sensitivity and specificity of 93% and 95%, respectively (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The definitive diagnosis is made using a biopsy or surgical procedure if the biopsy fails. In recent years, data show the delayed 18 F-FDG PET/CT method, with the aim of reducing misinterpretation and comparison of early and late SUVmax values, or the new calculation method, the relative activity distribution (rAD) method, can increase the differentiation between malignant and benign in PET/CT imaging (24,25). There are also studies that use different radionuclide agents such as 11 C-1-methionine and 18 F-fluoro-alphamethyl-tyrosine (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The proximal region of lesion was defined as the area near the ipsilateral hilar, and the area far from the ipsilateral hilar was defined as the distal region. [12] A 5-point scoring system was used to interpret the characteristics of FMSD, which represent the likelihood of the lesion being benign or malignant (Table 1). When the characteristics of FMSD in lesions are not obvious, the metabolic threshold can be manually adjusted on transverse PET images to assist the interpretation.…”
Section: Image Analysismentioning
confidence: 99%